Remediation of Wastewater Containing Heavy Metals Using Modified Diatomite - Visa, Maria; Luminita, Isac; Duta, Anca (Journal of Membrane and Separation Technology, 2014)
Diatomite, wood fly ash and their mixture with TiO2 were tested as adsorption substrates for copper and cadmium cations removal from wastewater. Raw diatomite and wood ash were pretreated and stabilized by washing and were comparatively investigated as adsorption substrates for heavy metals. Further on, a composite mix of pretreated diatomite and wood ash was obtained by mixing with nano-structured TiO2, to increase the surface area of the substrate materials. The novel adsorbent was investigated in terms of crystallinity (XRD), surface properties (AFM, SEM, porosity and BET surface) and surface chemistry (EDX, FTIR). Equilibrium studies demonstrated that the novel material has a high capacity for Cu2+ and Cd2+ removal, showing removal efficiencies above 80% for cadmium and of 99% for copper cations, in optimised adsorption experiments. In this paper the kinetic mechanisms of the cation adsorption are discussed and are correlated with the substrates properties.